Core Clinical Competencies in Counseling and Psychotherapy : Becoming a Highly Competent and Effective Therapist - Sperry, Len, author 324702; Sperry, Jon, author 653254 (New York, NY : Routledge, 2023)
Core Clinical Competencies in Counseling and Psychotherapy addresses the core competencies common to the effective practice of all psychotherapeutic approaches and includes specific intervention competencies of the three major orientations. This second edition emphasizes six core competencies common to the effective practice of all psychotherapeutic approaches. It includes the most commonly used intervention competencies of the cognitive-behavioral approaches—including Mindfulness-Based Cognitive Therapy, Dialectical Behavioral Therapy, and Acceptance and Commitment Therapy—psychodynamic approaches, and systemic approaches. This highly readable and easily accessible book enhances the knowledge and skill base of clinicians—both novice and experienced. The second edition has been fully revised throughout and includes a new appendix featuring handouts and worksheets. This book is essential to practicing clinicians and trainees in all mental health specialties, such as counseling, counseling psychology, clinical psychology, family therapy, social work, and psychiatry.